DNA adduct formation by the anticancer drug ellipticine in rats determined by 32P postlabeling - Stiborová, Marie; Breuer, Andrea; Aimová, Dagmar; Stiborová-Rupertová, Martina; Wiessler, Manfred; Frei, Eva (International journal of cancer, 2003)
Ellipticine is a potent antineoplastic agent whose mode of action is considered to be based mainly on DNA intercalation and/or inhibition of topoisomerase II. Recently, we found that ellipticine also forms covalent DNA adducts in vitro and that the formation of the major adduct is dependent on the activation of ellipticine by cytochrome P450 (CYP). Here, we investigated the capacity of ellipticine to form DNA adducts in vivo. Male Wistar rats were treated with ellipticine, and DNA from various organs was analyzed by (32)P postlabeling. Ellipticine-specific DNA adduct patterns, similar to those found in vitro, were detected in most test organs. Only DNA of testes was free of the ellipticine-DNA adducts. The highest level of DNA adducts was found in liver (19.7 adducts per 10(7) nucleotides), followed by spleen, lung, kidney, heart and brain. One major and one minor ellipticine-DNA adducts were found in DNA of all these organs of rats exposed to ellipticine. Besides these, 2 or 3 additional adducts were detected in DNA of liver, kidney, lung and heart. The predominant adduct formed in rat tissues in vivo was identical to the deoxyguanosine adduct generated in DNA by ellipticine in vitro as shown by cochromatography in 2 independent systems. Correlation studies showed that the formation of this major DNA adduct in vivo is mediated by CYP3A1- and CYP1A-dependent reactions. The results presented here are the first report showing the formation of CYP-mediated covalent DNA adducts by ellipticine in vivo and confirm the formation of covalent DNA adducts as a new mode of ellipticine action.
Keywords: Microsomes, Liver; Tissue Distribution; Rats; Male; orgánová specificita; mikrozomy; DNA Adducts; Rats, Wistar; mužské pohlaví; cytochrom P-450 CYP1A1; Organ Specificity; Antineoplastic Agents; Microsomes; krysa rodu Rattus; Cytochrome P-450 CYP1A1; Ellipticines; biotransformace; Biotransformation; cytochrom P-450 CYP1A2; protinádorové látky; zvířata; tkáňová distribuce; elipticiny; Cytochrome P-450 CYP1A2; jaterní mikrozomy; radioizotopy fosforu; potkani Wistar; Isotope Labeling; adukty DNA; Phosphorus Radioisotopes; izotopové značení; Animals